Distribución de Collisella atrata(Gastropoda) y redescripción de Zygantroplana ups (Platyhelminthes: Thrbellaria) - González, Norma Emilia (Universidad de Costa Rica, 1996)
The endernic distribution of the lirnpet Collisella atrata is confinned for the Gulf of California. The flatwonn species Zygantroplana ups is redescribed with live organisrns. Only sorne individuals have the tenninal notch rnentioned in the original description; tentacle ocelli rneasure 359-500urn; eyaculatory duct ends in a peneal bulb and has a thin stylet.